2005
DOI: 10.1107/s0909049505023575
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for reducing preferred orientation and strain in powder samples for high-pressure synchrotron X-ray diffraction in diamond-anvil cells

Abstract: Among the many problems associated with high-pressure X-ray diffraction from polycrystalline samples in the diamond-anvil cell are strain and preferred orientation. A method is presented for efficiently reducing preferred orientation of powder samples compressed in diamond-anvil cells to pressures in excess of 20 GPa. This method may be successfully applied to samples of yield strength higher than alkalihalides. In addition, the problem of strain is discussed using ice-VII as an example and as an illustration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Considering the literature reports on the stress-induced peak splitting for non ice systems [19][20][21][22][23][24][25] and for ice VII, 16 it is reasonable to suggest that the peak splitting observed in our study is a result of strain created during water-to-ice transformation. Indeed, stresses could be expected when growing ice crystals met at the interface with each other or a container wall, because water-to-ice transformation is accompanied by an approximately 10% volume increase.…”
Section: Resultsmentioning
confidence: 73%
“…Considering the literature reports on the stress-induced peak splitting for non ice systems [19][20][21][22][23][24][25] and for ice VII, 16 it is reasonable to suggest that the peak splitting observed in our study is a result of strain created during water-to-ice transformation. Indeed, stresses could be expected when growing ice crystals met at the interface with each other or a container wall, because water-to-ice transformation is accompanied by an approximately 10% volume increase.…”
Section: Resultsmentioning
confidence: 73%
“…Inaccuracies of the relative peak intensities are a frequent problem when measuring powder XRD in a diamond anvil cell due to the small sample mass and the presence of preferred orientations. 21 Therefore, the atomic positions of the pressure induced phase may be best determined from density functional theory calculations as reported previously, 10 rather than from refinements of XRD data. …”
Section: B X-ray Diffractionmentioning
confidence: 99%
“…microstrain increases with higher pressures and decreases after laser heating. The phenomenon of reflections narrowing after laser heating of a given sample in a DAC as a result of stress relaxation is known as laser annealing (Winkler et al, 2009;Tschauner et al, 2005). In this study, this effect could be shown quantitatively for the first time using microstrain parameters obtained from a Rietveld analysis.…”
Section: Figurementioning
confidence: 77%